Ta có {x4−y4=5446x3+27x2+10y3−75y2=−54x−250y$\Leftrightarrow \left\{\begin{array}{l}x^4+81=y^4+625\\12x^3+54x^2+54x=-20y^3+150y^2-500y\end{array}\right.⇔{x4−y4=544(x+3)4=(y−5)4\Leftrightarrow \left[\displaystyle{\begin{array}{l}\left\{\begin{array}{l}x^4-y^4=544\\x+3=y-5\end{array}}\right.\\\left\{x4−y4=544x+3=5−y\right.\end{array}\right.$$\Leftrightarrow \left[\begin{array}{l}\left\{\begin{array}{l}x=-5\\y=3\end{array}\right.\\\left\{\begin{array}{l}x=5\\y=-3\end{array}\right.\end{array}\right.$
Ta có
{x4−y4=5446x3+27x2+10y3−75y2=−54x−250y$\Leftrightarrow \left\{\begin{array}{l}x^4+81=y^4+625\\12x^3+54x^2+
108x=-20y^3+150y^2-500y\end{array}\right.
⇔{x4−y4=544(x+3)4=(y−5)4\Leftrightarrow \left[
\displaystyle{\begin{array}{l}\left\{\begin{array}{l}x^4-y^4=544\\x+3=y-5\end{array}}\right.\\\left\{
x4−y4=544x+3=5−y\right.\end{array}\right.$$\Leftrightarrow \left[\begin{array}{l}\left\{\begin{array}{l}x=-5\\y=3\end{array}\right.\\\left\{\begin{array}{l}x=5\\y=-3\end{array}\right.\end{array}\right.$